Estimasi Nilai Risiko Return Portofolio Saham LQ-45 dan JII dengan Copula Gaussian - Zuhra, Fatimah (Indonesian Journal of Business Economics and Management, 2022)
The purpose of an investor in investing in a stock portfolio is to maximize return and minimize risk. The most commonly used risk measure is Value at Risk (VaR) which can be calculated using a copula. The best copula is the Gaussian copula that can calculate the risk value in the combined distribution between LQ-45 returns and JII returns, which have a volatility effect so that it is modeled with the AR (1)-GARCH (1,1) model. With a 95% confidence level, the Gaussian copula has the smallest VaR value with the largest return.